Reliable and fast molecular sexing in Bos indicus cattle using amelogenin gene primers - Khaledi, Kourosh Jome; Panandam, Jothi Malar; Abdul Aziz, Maheran; Siraj, Siti Shapor (2009)
To investigate reliability of amelogenin gene primer pair for exon 5, SE47/SE48 for sex differentiation in Bos indicus three male and three female Brakmas (B. indicus) cattle were tested. The SE 47/48 primer pair generated PCR products of fragment length 280 bp for the females (AMELX) and fragments of 280 bp (AMELX) and 213 bp (AMELY) for the males. Thus the SE47/48 primer pair is not only reliable for sex differentiation in B. indicus but may also be used to differentiate the B. indicus and B. taurus males.